Bài 1:Tính:
a,(5x-y)2
b ( \(\dfrac{1}{4}\)+ y)2
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
a (3-2x)2 = 6 - 4x
b (xy+5)2 = 2xy + 10
c (2x+1)(1-2x) = 2x - 4x2 + 1 - 2x = 4x2 + 1
d (1-5x)3 = 3-15x
e (2x+y)(4x2 - 4xy + y2) = 8x3 -8x2y+2xy2 + 4x2y-4xy2 + y3 = 8x3 + y3 - 4x2y - 2xy2
`a, (3x+4)^2 = 9x^2 + 24x + 16`
`b, (5x-y)^2 = 25x^2 - 10xy + y^2`
`c, (xy - 1/2y)^2 = x^2y^2 - xy^2 + 1/4y^2`
a) \(\dfrac{x^2-2x+1-x^2-2x-1+4}{\left(x+1\right)\left(x-1\right)}=\dfrac{-4\left(x-1\right)}{\left(x+1\right)\left(x-1\right)}=\dfrac{-4}{x+1}\)
\(\dfrac{xy\left(x^2+y^2\right)}{xy\left(x^3\right)}.\dfrac{1}{x^2+y^2}=\dfrac{1}{x^3}\)
a: =1/2x^3*x^2-1/2x^3*6x-1/2x^3*10
=1/2x^5-3x^4-5x^3
b: =-3x^2*5x^3+3x^2*4x^2-3x^2*3x+3x^2*3x
=-15x^5+12x^4-9x^3+9x^2
c: \(=3x\cdot5x^2-3x\cdot2x-3x=15x^3-6x^2-3x\)
d: \(=\dfrac{1}{2}x^2y\cdot2x^3-\dfrac{1}{2}x^2y\cdot\dfrac{2}{5}xy^2-\dfrac{1}{2}x^2y=x^5y-\dfrac{1}{5}x^3y^3-\dfrac{1}{2}x^2y\)
`a, (3x+1)^2 = 9x^2 + 6x + 1`.
`b, (4x+5y)^2 = 16x^2 + 20xy + 25y^2`
`c, (5x-1/2)^2 = 25x^2 - 5x + 1/4`
`d, (-x+2y^2)^2 = x^2 - 2y^2x + 4y^4`.
`a)`
`(3x + 1)^2`
`= 9x^2 + 6x + 1`
`b)`
`(4x + 5y)^2`
`= 16x^2 + 40xy + 25y^2`
`c)`
`(5x - 1/2)^2`
`= 25x^2 - 5x + 1/4`
`d)`
`(-x + 2y^2)^2`
`= x^2 - 4xy^2 + 4y^4`
\(a,=4x^2+12xy+9y^2\\ b,=25x^2-10xy+y^2\\ d,=4x^2+4xy^2+y^4\\ e,=9x^4-12x^2y+4y^2\\ g,=x^3+64\)
a)\(25x^2-10x+y^2\)
b)\(\dfrac{1}{16}+\dfrac{1}{2}y+y^2\)